Novel energy and SLA efficient resource management heuristics for consolidation of virtual machines in cloud data centers. (October 2015) - Arianyan, Ehsan; Taheri, Hassan; Sharifian, Saeed
Highlights: A multi criteria resource allocation policy is proposed. A multi criteria policy for determination of underloaded PMs is proposed. A novel holistic resource management procedure is proposed. The results show up to 45% reductions in energy consumption. The results show up to 99% reductions in SLA violation. Abstract: Proliferation of IT services provided by cloud service delivery model as well as diverse range of cloud users have led to the establishment of huge energy hungry data centers all around the world. Therefore, cloud providers are confronted with great pressures to reduce their energy consumption as well as their CO2 emissions. In this direction, consolidation is proposed as an effective method of energy saving in cloud data centers. This paper proposes a new holistic cloud resource management procedure as well as novel heuristics based on multi-criteria decision making method for both determination of underloaded hosts and placement of the migrating VMs. The results of simulations using Cloudsim simulator validates the applicability of the proposed policies which shows up to 46%, 99%, and 95% reductions in energy consumption, SLA violation, and number of VM migrations, respectively in comparison with state of the arts.